Implementation of Engineering Professionalism in Construction Management on the Revitalization Project of SMKN 1 Jabon, Sidoarjo Regency - RIF'AN AHMADA (Fakultas Teknik Universitas Lampung, 2026)
This study examines the implementation of engineering professionalism in construction management on the Revitalization Project of SMKN 1 Jabon using the POAC approach. Data were collected from 36 project stakeholders and analyzed based on time, cost, and quality indicators. The findings indicate that professionalism and effective construction management significantly enhance project performance through proper planning, coordination, implementation, and supervision. The study concludes that engineering professionalism plays a vital role in improving project efficiency, effectiveness, and overall success, while providing practical guidance for construction practitioners and contributing to knowledge on construction management in educational infrastructure projects.